A hidden treasure of the Lower Pleistocene at Olduvai Gorge, Tanzania: The Leakey HWK EE assemblage. Issue 120 (July 2018) - Pante, Michael C.; de la Torre, Ignacio
Abstract: HWK EE is a little-known archaeological site from the top of Lower Bed II and the basal part of Middle Bed II, Olduvai Gorge, Tanzania. The site was originally excavated in the early 1970s by Mary Leakey, but the excavations and resulting lithic and fossil assemblages were never described. Here we report for the first time on the lithic and fossil assemblages that were recovered by Mary Leakey from the site. The lithic assemblage is one of the largest of any Oldowan site and is characterized by a core-and-flake technology with simple flaking techniques and minimal reduction of cores. Retouched flake frequencies and battered tools are higher than those reported for Olduvai Bed I and Lower Bed II assemblages, but flaking schemes are poorly organized. The fossil assemblage is well-preserved, taxonomically-rich, but dominated by bovids, and includes abundant feeding traces of both hominins and carnivores. Hominins are inferred to have broken the majority of limb bones at the site for access to marrow, while both carnivores and hominins likely had access to at least some flesh. HWK EE may represent one of the last Homo habilis sites at Olduvai Gorge, and is important to understanding the behavioral and cultural mechanisms that led to the emergence of the Acheulean and Homo erectus in the region.